THE DETERMINANTS OF THE COMPOSITE STOCK PRICE INDEX IN INDONESIA - Herry Krisnandi; Melati; Elwisam; Kumba Digdowiseiso; Latifah Abdul Ghani (CV. RADJA PUBLIKA, 2024)
This study employs a Systematic Literature Review (SLR) methodology to examine the factors that influence the composite stock price index in Indonesia. Identification of ten reputable journals using the Google Scholar search engine. The analysis findings from multiple journals, including the study conducted by Wahyuni et al. (2023) in the Consumer Goods Industry sector, indicate that inflation, dollar exchange rate, and Return on Equity (ROE) exert a substantial impact on IHSG. In a recent study conducted by Giffarina (2021), it was found that inflation and interest rates have a detrimental impact on the JCI, while the exchange rate also exerts a negative influence. This research validates prior perspectives, affirming that inflation and exchange rates exert a multifaceted influence on the Jakarta Composite Index (JCI) on the Indonesia Stock Exchange (IDX). This study offers a comprehensive perspective on the factors that impact the IHSG, thereby enhancing the comprehension of the Indonesian capital market for individuals involved in investment decision-making and policy formulation.